2016
DOI: 10.2320/matertrans.m2016078
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Thermal Expansion Coefficient of 18<i>R</i>-Synchronized Long-Period Stacking Ordered Magnesium Alloy

Abstract: We measured the thermal expansion coef cients of an 18R-synchronized long-period stacking ordered magnesium alloy (Mg 85 Zn 6 Y 9 ) and an α-phase pure magnesium (α-Mg). This was achieved by using a Gandol camera, which was attached on a high precision diffractometer at SPring-8 BL40XU beamline. By using this system, ne powder diffraction data could be obtained even from a highly oriented Mg 85 Zn 6 Y 9 polycrystal at different temperatures between 95 and 440 K. The thermal expansion coef cients along a-and c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The calculated result in Fig. 7(a) indicates the possibility of a transformation from hcp-Mg to an 18R structure above 420 K. This transformation has not been observed experimentally in pure Mg, 19) probably because of the high activation energy required for atomic displacement, as discussed in the previous work. 5) The following calculation was performed to make a case for a change in the lattice constant of the hcp-Mg by the release of a solution of Y and Zn from the D0 3 phase.…”
Section: Analysis Of Xrd Patternssupporting
confidence: 50%
See 1 more Smart Citation
“…The calculated result in Fig. 7(a) indicates the possibility of a transformation from hcp-Mg to an 18R structure above 420 K. This transformation has not been observed experimentally in pure Mg, 19) probably because of the high activation energy required for atomic displacement, as discussed in the previous work. 5) The following calculation was performed to make a case for a change in the lattice constant of the hcp-Mg by the release of a solution of Y and Zn from the D0 3 phase.…”
Section: Analysis Of Xrd Patternssupporting
confidence: 50%
“…A clear gap in the a value is observed, which almost coincides with the difference in the lattice parameter between the hcp and 18R-type LPSO structures observed in the MgYZn system. 19) The c value estimated from the (0002) hcp peaks collected over the entire experimental temperature range is shown by a gray cross in Fig. 3(b).…”
Section: Analysis Of Xrd Patternsmentioning
confidence: 99%
“…Diffraction experiments were performed with using a high precision diffractometer at the BL40XU beamline of SPring-8 [4]. A Gandolfi camera attachment was used to obtain fine diffraction patterns from oriented Mg 97 Zn 1 Y 2 alloy polycrystals [1]. The X-ray beam generated from the helical undulator was monochromatized with the Si(111) channel cut monochrometor and shaped by 150 × 150 μm 2 slits.…”
Section: Methodsmentioning
confidence: 99%
“…For structural materials, the thermal expansion often crucially affects mechanical strength. Recently, we succeeded to determine the thermal expansion coefficient of a single-phase 18R-LPSO Mg 85 Zn 6 Y 9 alloy [1]. This was achieved to use newly developed Gandolfi camera at the SPring-8 BL40XU.…”
Section: Introductionmentioning
confidence: 99%
“…This may due to the pure nickel coating of h-BN partially melted into the magnesium melt after the addition of h-BN particles. Studies have shown that the LPSO structure has a lower CTE than pure magnesium and good mechanical properties [10,11]. Therefore, Y element is added to the melt to consume Ni element, where the atomic ratio of Ni and Y is 1/1.6.…”
Section: Microstructure Of H-bn+lpso/mg Compositesmentioning
confidence: 99%